Strategi Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru di MI Al Mawaddah Warrahmah Kolaka - Heria; Suhrah; Aulia (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2025)
Apart from training and evaluation, school principals also try to create a conducive work environment for teachers. In interviews, the principal emphasized the importance of good communication between the principal, teachers and other staff. The active participation of the teachers shows that they are aware of the importance of self-development and improving the quality of teaching. Second, support from the Al Mawaddah Warrahmah Kolaka Islamic Boarding School Foundation through the Quality Assurance and Internal Supervisory Institute. As explained by Mrs. Nurfuadi, ideally each class would be taught by two teachers, but currently there is only one teacher for each class. This makes teachers' workload very heavy, so they have limited time to participate in training or other professional development activities.